تأخر ظهور المعاجم العربية الملايوية الثنائية دراسة تحليلية تأصيلية = The delay of compiling bilingual Arabic Malay dictionaries: an analytical study - Dollah, Nafi@Hanafi; Adam, Zalika (College of Islamic & Arabic Studies- UAE, DUBAI, 2017)
This paper seeks to focus on the conditions of compiling bilingual Arabic - Malay dictionaries in the 19th century in the world of the Malays whose population exceeds 230 million Muslims. The paper looks into the reasons behind the Malay scholars delaying the compiling of such dictionaries despite the fact that they were introduced to Islam in the early days of the Hijra. Moreover, the paper reviews the efforts of Malay lexicographers in transferring the Arabic words into Malay as well as clarifying the aspects of the development of such bilingual dictionaries and the impact of the monolingual dictionary that calls for the need for a comprehensive study of all factors: politically, socially, culturally or scientifically, that may affect such compilation in other nations. Regardless of such delay, researchers think that the compilation of bilingual Arabic – Malay dictionaries in the 19th century is logical – which doesn’t reflect the failure of Malay scholars towards studying, teaching and spreading Arabic language.